Research on satellite-ground adaptive modulation and coding techniques based on intellgent prediclion of channel state - JI Shuo; SUN Yaohua; PENG Mugen (Dianxin kexue)
In the scenario of direct mobile phone connection to low-earth orbit satellites, to address the issue of non-real-time feedback of channel quality indication information that adaptive modulation and coding techniques rely on, a channel state prediction model based on deep echo state network was proposed. Furthermore, an intelligent selection mechanism for modulation and coding schemes was introduced based on the prediction model, wherein the transmitter selects the modulation and coding scheme suited for the current channel conditions based on the channel prediction results. Simulation validation has demonstrated that adaptive modulation and coding based on channel prediction can improve the bit error performance of the link to a certain extent.